A Multi-Stakeholder Strategy in Digital Business Ecosystems: A Study of Technology-Based Firms - Muhammad Awaluddin; Gunadi Dwi Hantoro (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Digital business ecosystems have transformed how technology-based firms create sustainable value by encouraging collaboration among multiple stakeholders through digital platforms. However, the mechanisms through which multi-stakeholder strategies contribute to sustainable value creation remain insufficiently understood. This study aims to examine the influence of multi-stakeholder strategy on sustainable value creation by investigating the mediating role of digital platform capability, the moderating role of ecosystem governance, and the direct effect of technological capability. A quantitative research approach was employed using a cross-sectional survey of 210 managers and senior employees from technology-based firms. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that a multi-stakeholder strategy has a positive and significant effect on sustainable value creation. Digital platform capability significantly mediates this relationship, while ecosystem governance strengthens the effect of multi-stakeholder strategy on sustainable value creation. Technological capability also has a significant positive influence on sustainable value creation. These findings suggest that sustainable value creation in digital business ecosystems depends not only on stakeholder collaboration but also on digital platform capability, effective ecosystem governance, and strong technological capability, providing both theoretical and managerial insights for technology-based firms.